Fibrous dysplasia of the temporal bone - (:unkn) unknown (My University, 2000)
Fibrous dysplasia of the temporal bone is an extremely rare disorder. Here, a case of temporal bone fibrous dysplasia causing mild sensorineural hearing loss is presented. A heterogeneous solid mass destructing left mastoid bone and narrowing the external auditory meatus was found in the CT and MRI study of the temporal bone. The patient was treated surgically. Decompression of the external auditory canal and debulking of the expansile mass through a simple mastoidectomy was performed.
Keywords: Fibrous dysplasia; Hearing loss; Temporal bone; Vertigo